Identification and Analysis of the Polyhydroxyalkanoate-Specific β-Ketothiolase and Acetoacetyl Coenzyme A Reductase Genes in the Cyanobacterium Synechocystis sp. Strain PCC6803 - Taroncher-Oldenburg, Gaspar (American Society for Microbiology, 2000)
Synechocystis sp. strain PCC6803 possesses a polyhydroxyalkanoate (PHA)-specific β-ketothiolase encoded by phaA(Syn) and an acetoacetyl-coenzyme A (CoA) reductase encoded by phaB(Syn). A similarity search of the entire Synechocystis genome sequence identified a cluster of two putative open reading frames (ORFs) for these genes, slr1993 and slr1994. Sequence analysis showed that the ORFs encode proteins having 409 and 240 amino acids, respectively. The two ORFs are colinear and most probably coexpressed, as revealed by sequence analysis of the promoter regions. Heterologous transformation of Escherichia coli with the two genes and the PHA synthase of Synechocystis resulted in accumulation of PHAs that accounted for up to 12.3% of the cell dry weight under high-glucose growth conditions. Targeted disruption of the above gene cluster in Synechocystis eliminated the accumulation of PHAs. ORFs slr1993 and slr1994 thus encode the PHA-specific β-ketothiolase and acetoacetyl-CoA reductase of Synechocystis and, together with the recently characterized PHA synthase genes in this organism (S. Hein, H. Tran, and A. Steinbüchel, Arch. Microbiol. 170:162–170, 1998), form the first complete PHA biosynthesis pathway known in cyanobacteria. Sequence alignment of all known short-chain-length PHA-specific acetoacetyl-CoA reductases also suggests an extended signature sequence, VTGXXXGIG, for this group of proteins. Phylogenetic analysis further places the origin of phaA(Syn) and phaB(Syn) in the γ subdivision of the division Proteobacteria.